Dreaming equality : color, race, and racism in urban Brazil - Sheriff, Robin E., 1959- (Rutgers University Press, 2001)
"Brazil has the largest African-descended population in the world outside Africa. Despite an economy founded on slave labor, Brazil has long been renowned as a "racial democracy." Many Brazilians and observers of Brazil continue to maintain that racism there is very mild or nonexistent. The myth of racial democracy contrasts starkly with the realities of a pernicious racial inequality that permeates Brazilian culture and social structure. To study the significance of this contrast on African Brazilians views of themselves and their nation, Robin E. Sheriff lived in a primarily black shantytown in Rio de Janeiro, where she explored the inhabitantss views of race and racism firsthand. How, she asks, do poor African Brazilians experience and interpret racism in a country where its very existence tends to be publicly denied? How is racism talked about privately in the family and publicly in the communityor is it talked about at all? Sheriffs analysis is particularly important because most Brazilians live in urban settings, and her examination of their views of race and racism sheds light on common but underarticulated racial attitudes. This book is the first to demonstrate that urban African Brazilians recognize the deceptions of the myth of racial democracywhile embracing it as a dream of how their nation should be."--Book cover